2019
DOI: 10.1016/j.amjmed.2019.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Association of Hearing Impairment with Incident Depressive Symptoms: A Community-Based Prospective Study

Abstract: Objective: the aim was to investigate the potential association between hearing impairment and incident depressive symptoms. Methods: using a prospective community-based cohort study in France (the Paris Prospective Study III), participants aged 50-75 years were recruited between 2008 and 2012 and thereafter followed up every two years up to 2018. Hearing impairment, measured at study recruitment by audiometry testing, was defined as a pure tone average greater than 25 decibels in the better ear. Incident depr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 40 publications
2
24
1
Order By: Relevance
“…The findings from our systematic review and meta-analysis showed that hearing loss is associated with a very small increase in the odds of depression in older adults, 3 and this finding has been supported by a very small odds ratio also reported in the recent study by Lisan et al 1 We therefore recommend that future researchers exploring the association between hearing loss, depression, and other psychosocial factors that likely influence this relationship provide a more cautious interpretation of their findings and relevant effect sizes to ensure greater transparency in how we communicate our research to health care professionals and the broader scientific community. Blake J. Lawrence, PhD a Elise Alexander, BPsych (Hons) a Dona M.P.…”
supporting
confidence: 85%
“…The findings from our systematic review and meta-analysis showed that hearing loss is associated with a very small increase in the odds of depression in older adults, 3 and this finding has been supported by a very small odds ratio also reported in the recent study by Lisan et al 1 We therefore recommend that future researchers exploring the association between hearing loss, depression, and other psychosocial factors that likely influence this relationship provide a more cautious interpretation of their findings and relevant effect sizes to ensure greater transparency in how we communicate our research to health care professionals and the broader scientific community. Blake J. Lawrence, PhD a Elise Alexander, BPsych (Hons) a Dona M.P.…”
supporting
confidence: 85%
“…The clinical relevance of detection of mild (25-40 dB) hearing loss as it pertains to effectiveness of screening is uncertain because the only trial showing benefits of hearing aids among participants screen-detected limited eligibility to those with moderate (>40 dB) hearing loss. 44 Despite a relatively large body of observational studies indicating an association between hearing loss and higher rates of disability, 5 depressive symptoms, 7 cognitive decline, 8 and other adverse health and social outcomes, evidence on the efficacy of treatments for screen-detected hearing loss in primary care settings remains limited. The 6 included studies in this review are heterogeneous in terms of enrolled populations and amplification interventions; few reported on outcomes other than hearingrelated function, and follow-up duration was relatively short (ranging from 6 weeks to 4 months).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, sensory loss can impact the general health of the individual through social isolation, [27][28][29] decreased cognition, 7 and depressed mood. 30,31 This adverse impact on health would then be reflected in the individual's walking speed. It is possible then that addressing sensory loss and teaching compensatory strategies may mitigate at least some of the negative consequences of sensory loss on reduced walking speed.…”
Section: Discussionmentioning
confidence: 99%